2002
DOI: 10.1097/00000372-200208000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Extramammary Paget Disease of the Axilla Associated With Comedo-like Apocrine Carcinoma In Situ

Abstract: Extramammary Paget disease of the axilla with underlying apocrine carcinoma has been reported only in six cases until now. This report deals with a seventh case characterized by the unique finding of comedo-like features evocative of large cell ductal breast carcinoma within an otherwise typical in situ apocrine carcinoma. This is characterized by spiral-shaped foci of epithelial proliferation with decapitation secretion and central masses of necrotic debris. A possible connection between the solid neoplasm an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…our findings are consistent with previous research in the literature which showed that PCAC is negative for α-SMA (smooth muscle actin), a useful marker of myoepithelial cells (15,24). An ultrastructural study also found that PCAC, which displayed microvilli on the surface of the tumor cells under an electron microscope, showed differentiation into secretory cells (14,25).…”
Section: Intradermal Duct Secretory Portion Case --------------------supporting
confidence: 92%
“…our findings are consistent with previous research in the literature which showed that PCAC is negative for α-SMA (smooth muscle actin), a useful marker of myoepithelial cells (15,24). An ultrastructural study also found that PCAC, which displayed microvilli on the surface of the tumor cells under an electron microscope, showed differentiation into secretory cells (14,25).…”
Section: Intradermal Duct Secretory Portion Case --------------------supporting
confidence: 92%
“…' The published literature on in situ apocrine sweat lesions is scarce; however, there have been isolated case reports of pure in situ carcinoma. 1,2,4 Other invasive apocrine carcinomas of the skin that have contained an in situ component have also been previously described. 7,8 There have been a total of 9 cases of in situ sweat gland carcinoma, all of which were either high grade with comedonecrosis or with no specified grade mentioned.…”
Section: To the Editormentioning
confidence: 94%
“…7,8 There have been a total of 9 cases of in situ sweat gland carcinoma, all of which were either high grade with comedonecrosis or with no specified grade mentioned. 1,2,4,7,8 Of the cases that have specified a site of origin, all have occurred in the axilla; (the most common site of invasive apocrine carcinoma), or in the anogenital region where the so-called mammary-like glands (MLG) are found. 1,2,4,8 We have also recently seen 2 in situ apocrine lesions of the scalp; a previously unreported finding.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations